SURVEI MOTIVASI BEROLAHRAGA DI ERA NEW NORMAL PADA REMAJA USIA 13-17 TAHUN DI STADION H.M NURDIN PADANGSIDIMPUAN - Indah Permata Sari; Ardiah Juita; Niputu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research generally aims to determine and describe the motivation to exercise in the new normal era in adolescents aged 13-17 years at the H.M Nurdin Padangsdimpuan Stadium. The population in this research were teenagers aged 13-17 years who exercised at the H.M Nurdin Padangsdimpuan stadium. If the population size (N) is unknown, the sample size taken is calculated using the Lemeshow formula (1997), thus the number of samples in this research is 100 people. This research uses purposive sampling technique. The instrument in this research is a questionnaire with the Guttman scale. The results showed that 68 adolescents (68%) were included in the high category, 24 adolescents (24%) were included in the medium category, and 8 adolescents (8%) were included in the less category.Key Words: Motivation, Exercise, New Normal